PREPARATION AND IN VITRO EVALUATION OF FAST RELEASE DIAZEPAM SUPPOSITORIES FOR FEBRILE SEIZURES - Alsamman, Aseel; Othman, Mohammad (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The objective of this study was to optimize the best formula for fast release suppositories of diazepam. Methods: Suppositories were prepared by fusion method using Witepsol H15 as oleaginous base, polyethylene glycol as water-soluble polymer and poloxamer 188 as water miscible base. All suppositories were evaluated for physical characteristics, in vitro drug release and kinetic models. The effects of incorporating Tween 80 as a nonionic surfactant, propylene glycol as a cosolvent, and effervescent pair on the release rate of diazepam from suppositories were investigated. Differential scanning calorimetry and Fourier transform infrared spectrometry were used to characterize physical mixtures of diazepam and the different used bases. Results: Fast release of diazepam has been obtained from suppositories containing the effervescent pair. Many formulations of diazepam have been prepared and in vitro evaluated. PEG suppositories released diazepam more efficiently than poloxamer and Witepsol suppositories. The including of an effervescent pair in the formulation of suppositories greatly enhanced the release of diazepam. The addition of Tween 80 to Witepsol suppositories, PG to poloxamer suppositories, increased the rate and extent of diazepam release. Conclusion: Fast release of diazepam has been obtained from suppositories containing the effervescent pair (formula F3), which also have good physical properties.